2017
DOI: 10.1016/j.jvs.2016.11.055
|View full text |Cite
|
Sign up to set email alerts
|

The fate of endovascular aortic aneurysm repair after 5 years monitored with duplex ultrasound imaging

Abstract: Long-term follow-up of EVAR (mean, 7.5 years) revealed that approximately one in four patients will require intervention at some point during follow-up. First-time interventions were necessary in 22% of all patients in the first 5 years and in 6% of patients after 5 years, highlighting the need for continued graft surveillance beyond 5 years. All patients who had a first-time intervention after 5 years underwent an endoleak repair; none of these patients had a thrombosed limb or a rupture as a result of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
6
7
0
Order By: Relevance
“…This series of 22 patients is quite sizable, considering that 2 years before this report, the Vascular Low-Frequency Disease Consortium reported a total of 47 patients from 14 institutions with adventitial cystic disease. 1 The findings of the Consortium were essentially the same as from this report. Most (n ¼ 41) of lesions identified in the Consortium series were located in the popliteal artery, and 93% of the patients with lower extremity cysts had presented with claudication.…”
Section: Surgical Strategy To Reduce the Recurrence Of Adventitial Cysupporting
confidence: 73%
See 2 more Smart Citations
“…This series of 22 patients is quite sizable, considering that 2 years before this report, the Vascular Low-Frequency Disease Consortium reported a total of 47 patients from 14 institutions with adventitial cystic disease. 1 The findings of the Consortium were essentially the same as from this report. Most (n ¼ 41) of lesions identified in the Consortium series were located in the popliteal artery, and 93% of the patients with lower extremity cysts had presented with claudication.…”
Section: Surgical Strategy To Reduce the Recurrence Of Adventitial Cysupporting
confidence: 73%
“…Commentary: Although these authors reported a 16% reintervention rate after EVAR with a median follow-up of 4.5 years, our group documented that 28% of patients required reintervention for endoleak or graft limb stenosis/thrombosis after a longer mean follow-up of 7.5 years (range, 5.1-14.5 years). 1 We also reported a lower incidence of graft limb kinking/stenosis than reported in this study (ie, 3%-6%). 1,2 I am also surprised that endovascular techniques were used for only 40% of patients with endoleak or graft limb kinking/stenosis in their series.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…6 Despite low perioperative morbidity and mortality, the durability of EVAR is of concern as a high proportion of patients have continued perfusion of the AAA sac or endoleak. [7][8][9] Endoleak is the most common complication of EVAR and may be due to incomplete seal of the proximal or distal end of the graft (type I endoleak), reverse flow through collateral arteries (type II endoleak), or stent defects (types III-V). 10,11 Patients undergoing EVAR require long-term monitoring involving computed tomography or ultrasound to detect endoleak.…”
mentioning
confidence: 99%
“…In a study of patients observed for >5 years after EVAR at Pennsylvania Hospital and Danbury Hospital, first-time interventions were required in only 22% of patients during the entire first 5-year period. 1 Nonetheless, this study makes a provocative suggestion that we should coil embolize large patent IMAs when we perform EVAR. I suppose the authors are proposing that IMA embolization performed a couple of days before EVAR is technically easier, since the catheter can be advanced from the groin through the sac into the origin of the IMA, than after EVAR, which would require advancing a catheter through the superior mesenteric artery or internal iliac branches or between the graft and artery wall and then into the IMA.…”
mentioning
confidence: 85%